Optimizing Retail Store Operations Through Digitalization: Integration Of Qris Payment Methods, Implementation Of Portable Receipt Printers, And Preparation Of Goods Inventory Systems - Hamdani, Hamdani; Satryawati, Satryawati; Zuhriah, Zuhriah; Syawal , Lanang Fitrah; Mulia, Karina Tiara; Warsandi, Restu Pratama; Murzaki, Muhammad (PT Inovasi Pratama Internasional, 2025)
This study aims to improve operational efficiency at store Arif, a retail micro-enterprise, through operational digitization. Several solutions were implemented, including integrating the QRIS payment method to accelerate transactions and reduce manual errors, adopting portable receipt printers to expedite services and lower operational costs, and organizing inventory systems based on product categories to enhance stock management accuracy and efficiency. The methodology involved surveys, training, implementation, and monitoring. The results indicate that QRIS integration speeds up transactions and increases customer satisfaction, portable receipt printers reduce customer waiting times and paper waste, and inventory management based on product categories simplifies stock identification and procurement needs. In conclusion, the implemented digitization measures improved operational efficiency, customer satisfaction, and systematic stock management. Recommendations include continuous monitoring and development of the systems to adapt to market dynamics.